Avaliação do efeito de microplásticos de tinta spray em órgãos internos de operárias campeiras de Bombus atratus (Hymenoptera: Apidae, Bombini) - Boeing, Guilherme Andrade Neto Schmitz (Universidade Federal de São Carlos, 2024)
Recent studies have shown the negative environmental effects of spray paints due to microplastics (MPs) and their chemical composition. Photodegradation of these particles can increase the release of additives, including metals in the pigments. Neotropical bumblebees can be exposed to these contaminant particles, which have already been found in honey. Therefore, this study aimed to evaluate the effects of photodegradation on spray paints MPs exposed to different light intensities and exposure times, as well as assess the potential cytotoxicity of these pristine and photodegraded MPs on the columnar cells of the midgut, Malpighian tubules, and hepato-nephrocitic system cells of forager worker bees of Bombus atratus exposed to 50 mg.L-1 of MPs for 96 hours. Pristine microplastics were obtained through paint spraying, then characterized by shape and size. Portable X-ray fluorescence (XRF) and Fourier Transform Infrared Spectroscopy (FTIR) were used to determine elemental composition and polymer type. The MPs were then exposed to different intensities of UV-C radiation and exposure times. The release of potentially toxic elements (PTEs) by the MPs was quantified using an atomic emission spectrometer with microwave plasma. To assess the toxicity of the MPs, we conducted histological and histochemical analyses of the bee tissues. The XRF analysis revealed several elements in both paints, including five PTEs: Manganese, Chromium, Iron, Copper, and Zinc. The particles exposed to the highest UV-C intensity showed significant changes, such as superficial modification, blooming of additives, and surface detachment resulting in voids, altering their area and roundness values in relation to the pristine. Additionally, they exhibited an increase in the release of PTEs, especially Iron, Manganese, and Copper, which exceeded the safe limits set by the National Environment Council of Brazil (CONAMA). The increased release of PTEs is associated with the significant changes observed in the organs of bees exposed to the photodegraded MPs, which showed cellular vacuolization, nuclear condensation, and pyknosis. The release of PTEs from the photodegraded particles contributes to the disruption of the body homeostasis of the studied bees, potentially leading to reduced fitness and alterations in feeding and survival of the species. These findings underscore the importance of understanding the toxicity of environmentally realistic MPs, as plastic composition and weathering conditions can influence particle toxicity.
Evaluation of the effect of spray paint microplastics on the internal organs of foraging worker bees of Bombus atratus (Hymenoptera: Apidae, Bombini)
Keywords: Abelhas; Poliestireno; EPTs; Poluição Plástica; Bumblebees; Polystyrene; PTEs; Plastic Pollution; CIENCIAS BIOLOGICAS